Training of Paraeducators for Physical Education for Children with Visual Impairments. (January 2013) - Lieberman, Lauren J.; Conroy, Paula
Introduction: Children with visual impairments are often behind their peers in physical and motor skills. It is often necessary for these children to work one to one with a paraeducator to gain the benefits of physical education, improve physical activity and motor skills, and attain the basic standards of the Expanded Core Curriculum (ECC). Paraeducators are trained to work in classrooms, yet are rarely, if ever, trained in the subject of physical education. The purpose of the study presented here was to determine current training practices for paraeducators in the classroom and what is needed to ensure proper training for physical education for paraeducators who work with children with visual impairments. Methods: In the study, 143 professionals and parents were given a validated questionnaire related to the training needs of paraeducators for physical education. Results: The results indicated that although the majority of children with visual impairments attended physical education classes with their paraeducators, only 11% of the paraeducators were trained in physical education. The participants thought that the training should consist of safety practices, guiding techniques, teaching strategies, information on visual impairments, and most areas of the ECC. They thought that this information should be delivered in the form of a video or guest speakers and that the children with visual impairments should be included when possible. Discussion: Because of the large and varied sample in the study, the information gained could be used to create a training video for paraeducators who work with children with visual impairments in physical education. Implications for practitioners: The results of the study highlight areas that should be included as the foundation of training paraeducators for physical education.